PSYCHOLOGICAL CONDITIONS OF PERSONAL ENGAGEMENT AND DISENGAGEMENT AT WORK. - Kahn, W. A. (Academy of Management Journal, 1990)
This study began with the premise that people can use varying degrees of their selves, physically, cognitively, and emotionally, in work role performances, which has implications for both their wor...